External strengthening of reinforced concrete beam with opening by bamboo fiber reinforced composites - Chin, Siew Choo; Tee, Kong Fah; Tong, Foo Sheng; Doh, Shu Ing; Jolius, Gimbun (Springer Nature, 2020)
This paper presents the structural behaviour of reinforced concrete (RC) beams with and without openings strengthened externally with bamboo fiber reinforced composite (BFRC) plates in shear and flexure, respectively. Mechanical properties include tensile and flexural strength of epoxy, polyester and vinyl-ester based BFRC plates with 0%, 10%, 20%, 30% and 40% fiber volume fractions were evaluated. A total of fourteen beams were cast to evaluate the structural behaviour of RC beams strengthened with BFRC plates. All the beams were tested to failure under four-point bending. The results presented were in terms of load–deflection behaviour, failure mode and crack pattern. A comparison was also made between the performance of epoxy, polyester and vinyl-ester based BFRC plates in shear strengthening of RC beams with openings. Results revealed that the presence of openings in the shear zone reduced the original beam capacity of the control beam to about 52–55%. Shear strengthening of RC beams with openings using epoxy based BFRC plates showed significant improvement in regaining the beam structural capacity to approximately 32–36% higher than the un-strengthened beams. Meanwhile, strengthening of RC beams in flexure with epoxy based BFRC plates managed to regain the beam original capacity up to 98% of the control beam. Bamboo fiber composite reinforced with epoxy, polyester and vinyl-ester resins of 40% fiber volume fraction managed to regain the beam original capacity up to 82%. It was found that BFRC plates could divert and mitigate the formation of cracks away from the strengthened region as well as improved the beam ductility.